Driving factors and scenario prediction of carbon emission from transport sector in the Yangtze River Basin of China - Zhang, Panxing; Li, Songsong (Frontiers in Ecology and Evolution, 2023)
Climate change caused by carbon emission and their impact on social and economic system have garnered global attention, particularly from the world's largest emitters. Therefore, knowledge of both driving factors and reduction potential for carbon emission is crucial to revise climate policies. The transportation industry plays a major in global carbon emissions, mostly due to the excessive utilization of fossil fuels for combustion purposes. The goal of this study is to investigate the underlying causes that drive carbon emissions in China's Yangtze River Basin. Additionally, this study seeks to anticipate the future potential reduction in carbon emission. To achieve these, our research used a combination of the LMDI method and Monte Carlo simulation. The results indicate that, during 2006 to 2020, transportation carbon emission increased from 48.41 Mt to 104.37 Mt, following an annual growth rate of 5.64%, which suggests that energy strategies are not fully implemented as planned. The greatest positive impact on carbon emission is attributed to economic development, as the increase in resident income has led to the vigorous development of the transportation sector. Moreover, energy intensity and transportation efficiency have a negative influence on carbon emissions. The decrease of carbon emissions can be accomplished by the continued advancement of novel energy technologies and the optimization of energy systems. According to the baseline scenario, it is projected that carbon emissions from the transport sector will reach 198.76 Mt by the year 2030. Under the moderate scenario, there is a possibility for reducing emissions by 18.6 Mt, and under the advanced scenario, the potential reduction is estimated to be 48.84 Mt. As a view to suppress the increase of carbon emission from transportation, a set of plans and policies must be implemented from demand-side and supply-side, including improving transportation efficiency, and optimizing energy structure, etc.